The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1088/1475-7516/2005/04/005
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Van der Waals quintessence with observations

Abstract: Abstract. We discuss an alternative approach to quintessence modifying the usual equation of state of the cosmological fluid in order to see if going further than the approximation of perfect fluid allows to better reproduce the available data. We consider a cosmological model comprising only two fluids, namely baryons (modelled as dust) and dark matter with a Van der Waals equation of state. First, the general features of the model are presented and then the evolution of the energy density, the Hubble paramet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 52 publications
0
67
0
1
Order By: Relevance
“…As it is well known, the perfect fluid EoS is only a crude approximation of a real fluid that is usually used in cosmology since it represents the simplest way to fit the available data. However, as first shown in the Van der Waals quintessence scenario [29,30] and further demonstrated here, abandoning the perfect fluid EoS still makes it possible to fit the available astrophysical data with the same accuracy so that the use of realistic EoS turns out to be motivated also a posteriori. In our opinion, the era of precision cosmology calls for precision theory so that time is come to abandon approximate description such as the perfect fluid one.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As it is well known, the perfect fluid EoS is only a crude approximation of a real fluid that is usually used in cosmology since it represents the simplest way to fit the available data. However, as first shown in the Van der Waals quintessence scenario [29,30] and further demonstrated here, abandoning the perfect fluid EoS still makes it possible to fit the available astrophysical data with the same accuracy so that the use of realistic EoS turns out to be motivated also a posteriori. In our opinion, the era of precision cosmology calls for precision theory so that time is come to abandon approximate description such as the perfect fluid one.…”
Section: Discussionmentioning
confidence: 73%
“…Motivated by these considerations, it is therefore worth exploring what are the consequences of abandoning the perfect fluid EoS. A first step in this direction has been performed by Capozziello et al [29] who have considered a model in which a single fluid with a Van der Waals EoS accounts for both dark matter and dark energy (see also [30]). From classical thermodynamics, we know that the Van der Waals EoS is best suited to describe the behaviour of real gas with a particular attention to the phase transitions phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…For this, it is important to understand the evolution of structure formation in the VDW scheme. It was shown that for large redshifts the VDW model is similar to the ΛCDM model [4], where the VDW dark matter plays the role of a cosmological constant, showing that structure formation could evolve in a similar manner as in the ΛCDM model, although these points need to be further investigated [4]. Now, it was also shown that due to a negative adiabatic sound speed, perturbations are unstable in the VDW quintessence scenario, and inevitably the role of anisotropic stresses and entropy production has to be taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The accelerated and decelerated periods depend on the parameters, α, β and γ of the equation of state, and in the limiting case α, β → 0, one recovers the dark energy equation of state, with γ = p/ρ < −1/3. It was also stressed that the perfect fluid equation of state p = γρ reflects an approximation of cosmic epochs describing stationary situations, where phase transitions are not considered [4]. Thus, one of the advantages of the VDW model is that it describes the transition from a matter field dominated era to a scalar field dominated epoch, without introducing scalar fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation